POLICY CONSIDERATIONS IN PROVIDING PERFORMANCE ALLOWANCES FOR THE PROCESS OF EXAMINING DISCIPLINARY VIOLATIONS FOR STRUCTURAL OFFICIALS WITHIN THE MINISTRY OF LAW AND HUMAN RIGHTS IN VIEW OF DISTRIBUTIVE JUSTICE - Iswanti, Anis; Karim, Dr. (jfpublisher, 2024)
Performance allowances are one of the incentives often used in public administration to encourage employee performance. However, in the context of examining disciplinary violations against structural officials, careful policy considerations are necessary in order not only to focus on punishment, but also to encourage behavioral improvement. This research adopts the normative juridical method, which refers to regulations on Civil Servant discipline and provisions regarding the provision of performance allowances within the Ministry of Law and Human Rights, as well as other supporting regulations. This analysis aims to examine the considerations of direct superiors in granting performance allowances and the underlying distributive justice mechanism. The research highlights the critical role of direct supervisors in deciding performance allowances for structural officials involved in disciplinary violations. Key considerations include the severity of the violation, corrective actions taken, and the impact on the organization. Decisions should be evidence-based, fair, and aligned with effective personnel management principles, maintaining distributive justice to avoid discrimination or favoritism. Performance allowances should be granted based on objective criteria, such as actual performance and contributions to the organization, to uphold employee trust and morale. Transparent and measurable policies, along with clear communication between supervisors and officials, are essential for fair and sustainable management of performance allowances in the context of disciplinary reviews.